2011
DOI: 10.1159/000327939
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Overexpression Fails to Attenuate Hypertension when the Nitric Oxide Synthase System Is Not Fully Operative

Abstract: Heme oxygenase (HO) is an enzyme that is involved in numerous secondary actions. One of its products, CO, seems to have an important but unclear role in blood pressure regulation. CO exhibits a vasodilator action through the activation of soluble guanylate cyclase and the subsequent production of cyclic guanosine monophosphate (cGMP). The aim of the present study was to determine whether pathological and pharmacological HO-1 overexpression has any regulatory role on blood pressure in a renovascular model of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Studies on interaction of NOS and HO‐1 inhibition on BP were not consistent. For example, HO‐1 inhibition increased BP in NO‐depleted rats (Ushiyama et al ., ), or failed to trigger a pressor response when NOS was impaired (Polizio et al ., ). In the present study, all SnPP groups had higher level of NO metabolites than singly inhibited LNNA‐treated rats.…”
Section: Discussionmentioning
confidence: 96%
“…Studies on interaction of NOS and HO‐1 inhibition on BP were not consistent. For example, HO‐1 inhibition increased BP in NO‐depleted rats (Ushiyama et al ., ), or failed to trigger a pressor response when NOS was impaired (Polizio et al ., ). In the present study, all SnPP groups had higher level of NO metabolites than singly inhibited LNNA‐treated rats.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is particularly interesting because heme oxygenase-1 regulates eNOS function [55], its upregulation abrogates myocardial I/R injury [56][57][58] and gene therapy with heme oxygenase-1 has long-lasting cardioprotective effects [45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, among other functions, overexpression of HO has been shown to be cardioprotective [20]. Other authors also suggested that HO regulates blood pressure through CO only when the NOS pathway is fully operative, establishing a link between the role of NO and CO [21]. On the other hand, it was also recently shown that in VSM cells, thrombospondin-1, a matrix protein, can inhibit NO-stimulated sGC activation through binding to the cell surface receptor CD47 [22,23].…”
Section: Mechanisms Of Cyclic Nucleotide-mediated Vasorelaxationmentioning
confidence: 99%